STEM-BASED LEARNING IN THE 21ST CENTURY - Widodo, Muhammad Kholis (Proceeding of International Conference on Islamic Education (ICIED); Vol 5 No 1 (2020): Proceeding of International Conference on Islamic Education (ICIED), 2021)
In the 21st century, education is becoming increasingly important for shaping students to have learning and innovating skills, skills in using technology and information media, and also to be able to work, and survive using life skills. Based on pisa report, Indonesian children's language literacy, science and mathematics scores were on low rank. The Low literacy of Indonesian students in these three aspects is due to the low quality of human resources (teachers and education officer), the low quality and quantity of educational facilities and infrastructure, and the low quality of the learning process. Science learning in the context of technology and design is very potential to improve science literacy. science technology, engineering and mathematics (STEM), is a learning approach /model that is currently rebuilt in various developed countries such as America and. STEM-based learning is one of the potential alternative learning used to build 21st century skills. STEM-based learning can be packaged in terms of cooperative learning models, Problem based learning, Project based learning.